Circuit Model of Fano Resonance on Tetramers, Pentamers, and Broken Symmetry Pentamers - Attaran, A.; Emami, S.D.; Soltanian, M.R.K.; Penny, R.; Behbahani, F.; Harun, Sulaiman Wadi; Ahmad, Harith; Abdul-Rashid, H.A.; Moghavvemi, Mahmoud (Springer Verlag (Germany), 2014)
This paper presents the representation circuit model for Fano resonance of plasmonic nanoparticles in the optical domain. An intuitive explanation is provided for the physical nature of Fano resonance based on the three-level quantum system, and the Fano resonance effects of three basic nanoparticle arrangements, namely tetramer, pentamer, and symmetry broke pentamer are discussed. A coupling capacitor is calculated as an equivalent component in the proposed circuit model in order to describe the coupling effect between subradiant and superradiant mode in the Fano resonance. The circuit impedances of tetramer, pentamer, and broken symmetry pentamer are simulated, with resultant circuit models in agreement with the calculated results based on S-parameters.